2017
DOI: 10.17159/2309-8309/2017/v16n4a8
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of acute traumatic occupational hand injuries seen at a South African state hospital

Abstract: Background: Acute traumatic occupational hand injuries are the second most common cause of all traumatic hand injuries worldwide and the most commonly injured body part during occupational accidents. Traumatic hand injuries account for approximately one-third of all traumatic injuries seen at state hospitals in South Africa. The aetiology of occupational hand injures in South Africa is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In lower-to-middle income countries (LMIC), the prevalence of THI is lower with a study in Uganda, reporting the burden of hand injuries to be 5.5 per cent in trauma services 6 . However, Stewart and colleagues in their study 17 indicated that THI accounted for one-third of all traumatic injuries treated at South African public sector hospitals.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…In lower-to-middle income countries (LMIC), the prevalence of THI is lower with a study in Uganda, reporting the burden of hand injuries to be 5.5 per cent in trauma services 6 . However, Stewart and colleagues in their study 17 indicated that THI accounted for one-third of all traumatic injuries treated at South African public sector hospitals.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Both international and local literature highlights that THI's vary in severity and complexity and may severely affect a person's ability to perform daily activities [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . International literature highlights that THI's vary in severity and complexity and may severely affect a person's ability to perform daily activities as well as their life roles, either temporarily or permanently 7,23,24 .…”
Section: Literature Review Traumatic Hand Injuriesmentioning
confidence: 99%
“…In South Africa, high rates of interpersonal violence and road accidents (when compared to global statistics 14 ), are reported to contribute to a higher incidence of hand injuries 15 . Moreover, the high rates of work-related hand injuries amongst workers who engage in manual labour, the traumatic injuries seen within South African state hospitals 16,17 together with patients presenting to occupational therapy with firework injuries 6 and tendon injuries 5,7,18 imply a high prevalence of hand injuries with wounds. Wounds may include, amongst others, abrasions, bites, surgical wounds and traumatic wounds 1 .…”
Section: Prevalence Of Wounds In Hand Injuries In South Africamentioning
confidence: 99%
“…For clients who are breadwinners, the indirect costs to their family and community are extensive. In a study conducted in a tertiary hospital in South Africa, 85% of the hand injury clients interviewed earned less than 600US$ monthly (between R1,000 and R9,000 per month), despite being the breadwinners of their family 38 . It is likely that a breadwinner in South Africa who is earning minimum or close to minimum wage, will experience significant financial stress if they are unable to work for any length of time, which highlights the need for further studies to understand the value of financial compensation for breadwinners who have been injured.…”
Section: Assets and Barriersmentioning
confidence: 99%